Comparison of the population structure of the fiddler crab Uca vocator (Herbst, 1804) from three subtropical mangrove forests - Colpo, Karine Delevati [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Editorial CSIC, 2004)
The population structure of U. vocator was investigated during a one-year period in three mangrove forests in southeast Brazil. The study specifically addressed comparisons on individual size juvenile recruitment and sex-ratio. The structure of the mangrove forests, i.e. density, basal area, and diameter, and the physical properties of sediments. i.e. texture and organic matter contents, were also examined. A catch-per-unit-effort (CPUE) technique was used to sample the crab populations using 15-min sampling periods by two people. Males always outnumbered females, probably due to ecological and behavioural attributes of these crabs. The median size of fiddler crabs differed among the sampled populations. The mangroves at Indaiá and Itamambuca showed higher productivity than those at Itapanhaú, where oil spills impacting the shore were reported. Marked differences were found regarding individual size, either their size at the onset of sexual maturity or their asymptotic size, suggesting that food availability may be favouring growth in the studied populations.
Keywords: Mangrove crab; Ocypodidae; Population structure; Uca vocator; body size; crab; mangrove; population structure; recruitment; sex ratio; Brazil; South America; Decapoda (Crustacea); Halophila; Rhizophoraceae; Scylla; Uca